Digital Hazards for Feeding and Eating: What We Know and What We Don't - Ioannidis, Konstantinos (Curr Psychiatry Rep, 2021)
PURPOSE OF REVIEW: We aimed to accrue recent evidence exploring effects of modern online activities (e.g., Internet use) on feeding and eating disorder symptoms, and related traits. We examined available evidence to ascertain any direct influences from online activities on feeding and eating disorders, thereby shedding light on putative mechanisms by which those influences may occur. RECENT FINDINGS: Many facets of problematic usage of the Internet correlate cross sectionally with eating disorder and related psychopathology. There is evidence to suggest that significant effects do exist in the direction of specific Internet activities contributing to eating disorder symptoms, viewed dimensionally. Putative mechanisms are discussed. However, a significant number of eating disorder phenotypes and Internet-related activities remain under-researched. SUMMARY: Specific facets of engagement with the online environment appear to confer risk for feeding and eating problems, evidence being strongest for non-clinical studies using dimensional measures. More research is required to rigorously confirm causal effects, including in patients meeting formal diagnostic criteria for eating disorders. We also highlight the need for high-quality evidence to explore how eating disorder phenotypes are commonly as well as uniquely affected by different online activities. Such research is needed in order that scientific understanding in this area can be translated to protect those most at risk of disordered eating, including through changes in public health approaches and clinical practice.